The development and feasibility of gamified digital intervention aiming to promote physical activity in early childhood - Pakarinen, Anni (fi=Turun yliopisto|en=University of Turku|, 2018)
This study aimed to develop a gamified digital intervention aiming to promote physical activity in early childhood. A further aim was to evaluate the feasibility of the intervention among the target group in child health clinics. The study consists of two phases. The development phase – a cross-sectional correlational study explored developmental factors associated with active play behaviour of 2.5-year-old toddlers (n = 717). Data were collected in child health clinics and consisted of the assessment of child’s neurological development and preference to participate in active play. Data were analyzed statistically. The results showed that delayed gross motor skills, self-help skills and auditory perception were negatively associated with a child’s preference to participate in physically active play. A quantitative systematic review explored previous gamified digital interventions that enhanced the physical activity self-efficacy of children. Data were collected from five electronic databases and analyzed narratively and statistically. The results showed that the gamified digital interventions are effective in enhancing the physical activity self-efficacy of children. The results from a correlational study and systematic review, together with National Physical Activity Recommendations, contributed to the development of the intervention. The feasibility and piloting phase – a mixed-method post-test feasibility study – evaluated the usability and acceptability of the intervention from the perspective of public health nurses (n = 5) and families with a child either 1.5 or 4 years old (n = 15). Data were collected using questionnaires and interviews, and analyzed statistically and with deductive qualitative content analyses. The results showed that the intervention was usable and acceptable. Suggestions for further development of the intervention consisted of simplifying the intervention, adding more gamified elements to be more attractive to children and adding more precise feedback for the parents. Based on these results, the intervention was modified and a cluster-randomized controlled study was planned to evaluate the effectiveness of the intervention.

Varhaislapsuuden fyysistä aktiivisuutta edistävän pelillisen digitaalisen intervention kehittäminen ja soveltuvuus Tämän tutkimuksen tarkoituksena oli kehittää pelillisyyttä hyödyntävä digitaalinen interventio lasten fyysisen aktiivisuuden edistämiseen lastenneuvoloissa, sekä arvioida intervention soveltuvuutta lasten, perheiden ja terveydenhoitajien näkökulmasta. Tutkimus koostuu kahdesta vaiheesta. Kehittämisen vaiheessa, korrelatiivinen poikkileikkaustutkimus tutki 2,5-vuotiaiden lasten (n=717) kehityksen ja liikunnallisen leikin välisiä yhteyksiä. Aineisto kerättiin lastenneuvoloissa ja se koostui lasten neurologisen kehityksen arvioinneista ja liikunnalliseen leikkiin osallistumisen arvioinneista. Aineisto analysoitiin tilastollisin menetelmin. Tulosten mukaan motorinen kehitys, omatoimisuus ja kuullun ymmärtäminen olivat yhteydessä lapsen liikunnalliseen leikkiin osallistumiseen. Kvantitatiivisen systemaattisen katsauksen tarkoituksena oli tarkastella aiempia pelillisiä interventioita lasten fyysisen aktiivisuuden minäpystyvyyden edistämisen näkökulmasta. Aineisto kerätiin viidestä sähköisestä tietokannasta ja analysoitiin narratiivisesti ja tilastollisin menetelmin. Tulosten mukaan peli-interventiot ovat tehokkaita lasten fyysisen aktiivisuuden minäpystyvyyden edistämisessä. Korrelatiivisen tutkimuksen ja katsauksen tulokset sekä kansalliset lasten liikunnan suositukset toimivat intervention kehittämisen pohjana.  Soveltuvuuden ja pilotoinnin vaiheessa, monimenetelmäinen soveltuvuustutkimus arvioi intervention käytettävyyttä ja hyväksyttävyyttä terveydenhoitajien (n=5) sekä 1,5- ja 4-vuotiaiden lasten ja heidän perheidensä (n=15) näkökulmasta. Aineisto kerättiin kyselyin ja haastatteluin sekä analysoitiin tilastollisin menetelmin ja laadullisella deduktiivisella sisällön analyysilla. Tulosten mukaan interventio oli käytettävä ja hyväksyttävä. Tutkittavat toivat esiin intervention parantamisehdotuksia, jotka liittyivät intervention sujuvuuden ja pelillisten elementtien lisäämiseen sekä vanhemmille osoitetun yksityiskohtaisemman palautesysteemin luomiseen. Soveltuvuustutkimuksen tulosten perusteella interventiota muokattiin ja intervention vaikuttavuuden tutkimus suunniteltiin satunnaistettuna kontrolloituna tutkimuksena.